Emotional work in occupational groups of Latin America: A scoping review - Ramírez-Sánchez, Juan Camilo; Solarte-Tobar, María Camila; Bastidas-Jurado, Claudia Fernanda; Matabanchoy-Salazar, Johana Madelyn (Universidad y Salud, 2022)
Introduction: Emotional work deteriorates the mental health of employees who interact with the public and therefore must regulate their emotions in order to express those established by the organization. Objective: To systematically map the main findings of Emotional Work in occupational groups of Latin America based on the revision of scientific articles published between 2009 and 2020 through a scoping review. Materials and methods: A PRISMA-ScR methodology with the keywords “trabajo emocional” (Spanish), “emotional labor”/“emotional work” (English) and “trabalho emocional” (Portuguese) was used to search the following databases: LILACS, Redalyc, Dialnet, DOAJ, BVS, Gale One File: Psychology and EBSCOhost. A document record matrix was used as format for data graphic. Results: From 186 articles, 17 were selected with the following characteristics: majority were from Brazil; included health employees and professors; defined emotional work using 6 categories; used 11 measurement instruments. Conclusions: There is a wide understanding of the topic of emotional work, however the evidence in Latin America is limited, which is why it is necessary to continue investigating its incidence in different work environments in order to obtain a global understanding of the construct.